Green Marketing and Green Purchase Intention: The Mediating Role of Brand Perception - Dewi Murtiningsih; Junaedi Junaedi (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Green marketing is the marketing of products that are considered safe from an environmental perspective, environmentally friendly marketing that combines various activities such as product redesign, changes in production processes, changes in product packaging used and changes in advertising. This study aims to determine the effect of green marketing on green brand awareness and green brand image, as well as its direct and indirect influence through mediation on environmentally friendly purchasing intentions. This study uses an explanatory research design with a sampling technique using purposive sampling, the number of samples determined using the maximum likelihood estimation formula, and the sample used in this study was 187. Data were processed using PLS. The results of the study indicate that marketing influences green purchasing intentions, green marketing does not influence green brand awareness, green brand awareness influences green purchasing intentions, green brand awareness mediates the influence of green marketing on green purchasing intentions, green marketing influences green brand image, green brand image on green purchasing intentions, green image mediates the influence of green marketing on green purchasing intentions.